Secure and Authenticated Cryptographic Techniques: “A Review” - Srivastav, S; Gupta, V; Gola, K.K (International Journal of Computer Sciences and Engineering, 2025)
In the world of the high technology networking system, it is very important to ensure the security of the data. To make our data secure during communications, Cryptography is the best method in networking security to provide the confidentiality or authentication. There are two main methods which are used to achieve these two things (i.e. confidentiality and authentication) in cryptography that are public key cryptosystem and digital signatures. Here this work shows a survey on the existing techniques and also presents a comparison that helps the researches to find the gaps in the existing techniques.